Semi-collusion and innovation: friends or foes? - Basak, Debasmita; Mukherjee, Arijit (Oxford Economic Papers, 2026)
It is commonly held that firms engaging in collusive activities adversely affect firms' R&D incentives and social welfare. With a stochastic non-tournament R&D competition, we argue that this pessimistic view does not necessarily hold when firms collude in production but compete in other non-production activities, such as R&D. This phenomenon is known as semi-collusion. Adopting a unified R&D model that encompasses both product and process R&D, we show that if the probability of success in R&D is relatively high (low), semi-collusion may provide higher (lower) innovation incentives compared to a non-cooperative setting when the firms invest in process innovation. The innovation incentives are strictly higher under semi-collusion when the firms invest in product innovation. Additionally, we find that regardless of the type of innovation (process or product R&D), semi-collusion may improve social welfare when the firms compete in prices and the goods are close substitutes.